Penerapan Pelayanan Kesehatan dan Keselamatan Kerja pada Perawat IGD Rumah Sakit Umum Dr. Wahidin Sudiro Husodo Mojokerto tahun 2017 - Widiwati Rinjani; AT Diana Nerawati; Ernita Sari (GEMA LINGKUNGAN KESEHATAN, 2018)
Hospital is a health service unit for community, has potential hazards such caused by physical, chemical, biological and ergonomic and psychosocial factor thus a hospital is demanded to conduct integrated OHS so then Occupational Disease and Occupational Accidents risk can be avoided. Based on preliminary survey in Dr. Wahidin Sudiro Husodo Regional General Hospital of Mojokerto in last a year had occurred 1 (one) occupational accident in Emergency Department that was accidentally punctured by patient’s needle stick. The aim of this study is to determine the implementation of occupational health and safety service in Emergency Department.This study used descriptive research type with the number of sample was 18 Emergency nurses. The data collection was done by interview and observation.The results of study showed the implementation of occupational health was 30% had met the requirements, enough to meet the requirements was 40% on variables of regular medical check up, ill employees medication and treatment, occupational environment also ergonomic and registration report evaluation to hospital Director. Less to meet the requirements was 30% on variables of pre working medical check up, particular medical check up and surveillance activity. While in occupational safety service was 80% had met the requirements, enough to meet the requirements was 10% on and regostration report evaluation to hospital Director variable and 10% less met the requirements on the proper of hospital occupational equipments variable.The conclusion of occupational health service implementation was 30% had met the requirements while occupational safety service implementation was 80% had met the requirements. It is advised to improve the implementation of occupational health and occupational safety service such as reporting and registration of occupational health and accidents. Keywords      : Occupational Health and Safety Service